The versatile synthesis of polyhedron core/shell/shell Cd0.1Zn0.9Se/CdxZn1-xS/ZnS quantum dots - Loghina, Liudmila; Chylii, Maksym; Kadeřávková, Anastasia; Houdek, Jakub; Vlček, Miroslav (IEEE (Institute of Electrical and Electronics Engineers), 2022)
One of the most effective strategies for reducing the surface defects in nanocrystals is the shell growth on the already formed cores. This approach provides not only an increase in the photoluminescence quantum yield (PL QY) but also prevents the diffusion of cations and anions from the core material. Gram scale synthesis of the green-emitting core (10 g) was performed by interaction of highly reactive substituted selenourea ((Z) - N -(octadec-9-enyl)morpholine-4-carboseleno-amide) with the cadmium and zinc linoleates mixture at 240 °C. Verification of the shell growth method based on the volume ratios of the core and the core with a shell led to the creation of a series of core/shell/shell Cd0.1Zn0.9Se/CdxZn1-xS/ZnS(x=0.1;0.25;0.4;0.6;0.75) quantum dots (QDs). Deposition of the first shell (Z)-1-(octadec-9-enyl)-3-phenylthiourea) of CdxZni-xS composition with a thickness of 2 monolayers (MLs) (epitaxial growth) resulted in blue x=0.1 and 0.25) and red (x=0.4;0.6 and 0.75) shifts in emission bands and an increase in PL QY (up to 71 %). The deposition of the second shell (ZnS, 2 MLs), the same for all compositions, was not epitaxial to the corresponding cores (Cd0.1Zn0.9Se/CdxZn1-xS), which brought the significant changes in QDs shape. This phenomenon did not negatively affect the optical properties of Cd0.1Z n0.9Se/CdxZn1-xS/ZnS QDs, but even led to some improvements. The analysis of Cd0.1Zn0.9Se/CdxZn1-xS/ZnS core/shell/shell by EDS, XPS, and XRD methods, confirmed the accordance of the initial ratios with the given compositions and sizes.
Univerzální syntéza polyedrických core/shell/shell Cd0.1Zn0.9Se/CdxZn1-xS/ZnS kvantových teček
Keywords: core/shell/shell quantum dots; methodology; photoluminescence; substituted selenourea; substituted thiourea; core/shell/shell kvantové tečky; metodologie; fotoluminiscence; substituovaná selenomočovina; substituovaná thiomočovina